A high-performance carbon nanoparticle-decorated graphite felt electrode for vanadium redox flow batteries. (15th August 2016) - Wei, L.; Zhao, T.S.; Zhao, G.; An, L.; Zeng, L.
Highlights: Propose a carbon nanoparticle-decorated graphite felt electrode for VRFBs. The energy efficiency is up to 84.8% at 100 mA cm −2 . The new electrode allows the peak power density to reach 508 mW cm −2 . Abstract: Increasing the performance of vanadium redox flow batteries (VRFBs), especially the energy efficiency and power density, is critically important to reduce the system cost to a level for widespread commercialization. Unlike conventional VRFBs with flow-through structure, in this work we create a VRFB featuring a flow-field structure with a carbon nanoparticle-decorated graphite felt electrode for the battery. This novel structure, exhibiting a significantly reduced ohmic loss through reducing electrode thickness, an increased surface area and improved electrocatalytic activity by coating carbon nanoparticles, allows the energy efficiency up to 84.8% at a current density of as high as 100 mA cm −2 and the peak power density to reach a value of 508 mW cm −2 . In addition, it is demonstrated that the battery with this proposed structure exhibits a substantially improved rate capability and capacity retention as opposed to conventional flow-through structured battery with thick graphite felt electrodes.